2000
DOI: 10.1182/blood.v96.13.4246
|View full text |Cite
|
Sign up to set email alerts
|

Fyn and Lyn phosphorylate the Fc receptor γ chain downstream of glycoprotein VI in murine platelets, and Lyn regulates a novel feedback pathway

Abstract: Activation of platelets by collagen is mediated by the complex glycoprotein VI (GPVI)/Fc receptor γ (FcRγ chain). In the current study, the role of 2 Src family kinases, Fyn and Lyn, in GPVI signaling has been examined using murine platelets deficient in one or both kinases. In the fyn−/−platelets, tyrosine phosphorylation of FcRγ chain, phopholipase C (PLC) activity, aggregation, and secretion are reduced, though the time of onset of response is unchanged. In the lyn−/−platelets, there is a delay of up to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 25 publications
2
68
0
1
Order By: Relevance
“…Activation of RAS by G coupled‐receptors in other cell types is also mediated through the SRC kinases [17–19]. PP1 also inhibited activation of RAS stimulated by convulxin, consistent with the role of these kinases in mediation of the phosphorylation of the ITAM motif of the Fc receptor γ chain [11,12].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Activation of RAS by G coupled‐receptors in other cell types is also mediated through the SRC kinases [17–19]. PP1 also inhibited activation of RAS stimulated by convulxin, consistent with the role of these kinases in mediation of the phosphorylation of the ITAM motif of the Fc receptor γ chain [11,12].…”
Section: Discussionmentioning
confidence: 63%
“…SRC family kinases are necessary for the initial signalling events induced by GPVI, notably for phosphorylation of the GPVI‐associated receptor FcR γ‐chain [11,12]. As expected, the SRC kinase family inhibitor PP1 inhibited convulxin‐induced ERK and RAS activation (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Platelets express several SFK members, and it has been proposed that certain SFKs regulate different aspects of platelet signalling [16]. The role played by Lyn in platelet activation is particularly complex, since Lyn deficiency was found to initially delay signalling, but subsequently potentiate responses such as spreading and aggregation, in platelets activated via GPVI, suggesting that Lyn both facilitates GPVI signal transduction and participates in a novel inhibitory pathway in platelets [10]. In support of a negative regulatory role for Lyn in platelets, Maxwell et al [48], have shown previously that platelets deficient in either Lyn or the inositol phosphatase, SHIP (SH2containing inositol phosphatase-1), exhibit enhanced spreading on fibrinogen and calcium mobilization, suggesting that both Lyn and SHIP act as negative regulators of α IIb β 3 -mediated outside-in signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Agonist-induced platelet activation results in activation of the platelet-specific integrin, α IIb β 3 , which binds fibrinogen and VWF, and enables platelet aggregation [7]. SFKs (Src family kinases) have been shown to play important roles in platelet activation, aggregation and adhesion [8][9][10][11]. Platelets express six SFKs, including p60 Src [12][13][14][15], p59 Fyn [14][15][16][17], p56 Lck [15,17], p62 Yes [15,18], p55 Fgr [15] and p53/56 Lyn [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Обоснование кровоточивости Можетпоказаться,чтогеморрагическиеэпизоды натерапииибрутинибомсвязанысингибированием Btk, которая также экспрессируется в тромбоцитах ивовлеченавсигнальныепути,стимулируемыерядом ключевыхрецепторов.Какпоказываютфункциональные тесты, у пациентов, получающих ибрутиниб, снижена функциональная активность тромбоцитов вответнастимуляциюколлагеном [16].Сколлагеном тромбоциты взаимодействуют через интегрин α2β1, ответственныйзаадгезиюиприкреплениетромбоцита к коллагеновому матриксу, рецептор GPVI (glycoprotein VI), опосредующий внутриклеточный сигналингвответнаколлагеновуюстимуляцию,ире-цепторGPIb-V-IX,которыйспособенкопосредованномувзаимодействиюсколлагеномчерезфакторфон Виллебранда(VWF) [18].GPVI,входящийвсуперсемейство иммуноглобулинов, нековалентно связан сγ-цепьюFc-рецептора(FcRγ) [19].GPVIпослевзаимодействиясосвоимлигандомчерезфосфорилирова-ниепоследовательностиITAM(immune-receptortyrosine-based activation motif) и цитоплазматический доменFcRγспособствуетактивациифосфокиназFyn иLyn [20].ФосфорилированиеITAMтакжеспособст-вуетактивациитирозинкиназыSyk,котораяучаствует вформированиисигнальногокомплекса,состоящего избелковLAT,SLP-76,Btk,GadsифосфолипазыCγ2 [21],чтообеспечиваетдальнейшуюпередачусигнала сучастиемМАР-киназ(МАРK),синтезтромбоксана А2(ТХА2),секрециюгранулиактивациюинтегринов (см.рисунок) [22].…”
Section: частота геморрагических осложненийunclassified